PERLINDUNGAN HUKUM TERHADAP NASABAH PENYIMPAN DANA BANK TERKAIT DENGAN DATA NASABAH DALAM TRANSAKSI ELEKTRONIK - Suparta Bonantara, I Dewa Gede; Wirasila, Anak Agung Ngurah (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013)
Legal protection for bank depositors associated with customer data in electronictransactions knowing how to protect and safeguard the data bank depositors inelectronic transactions including reviewing the law with a view of the gaps in the normor principle of law by examining primary legal materials and secondary legal materialsand find out the truth by using the method of deductive reasoning. Implicit depositperotection, Explicit deposit protection, Prudential principles.
Keywords: Legal Protection, Depositor, Electronic Transactions